Current and future applications of brain magnetic resonance imaging in ARSACS - Alessandra Scaravilli; Davide Negroni; Claudio Senatore; Filippo Maria Santorelli; Sirio Cocozza (The Cerebellum, 2025)
Magnetic Resonance Imaging (MRI) is a tool with an unquestionable role in the study of neurodegenerative disorders, both for diagnostic purposes and for its ability of providing imaging-derived biomarkers with a growing central role as reliable outcomes in clinical trials. This is even more relevant when dealing with rare disorders such as the Autosomal Recessive Spastic Ataxia of Charlevoix-Saguenay (ARSACS), in which the search of diagnostic and prognostic biomarker is crucial. Due to the rarity of this condition, a comprehensive knowledge of MRI signs observed in ARSACS is lacking. Furthermore, many domains remain still unexplored in ARSACS, especially with reference to the application of advanced imaging techniques that could shed light on the pathophysiological mechanisms of brain damage in this disorder. In this review, after a brief introduction on the major conventional and advanced MRI techniques that can used for diagnostic and research purposes, we present current neuroradiological knowledge in ARSACS. Having discussed strength and weak points of conventional and advanced imaging findings, we also suggest possible future research in this neurologically complex clinical condition.

Molecular composition and possible transformations of labile soil organic matter fractions in Mediterranean arable soils: Relevance and implications - Hamada Abdelrahman; Diana Hofmann; Rachel L. Sleighter; Daniel C. Olk; Anne E. Berns; Teodoro Miano; Sabry M. Shaheen; Claudio Cocozza (Environmental Research, 2023)

Use of constructed wetlands to prevent overloading of wastewater treatment plants - Claudio Cocozza; Claudio Di Iaconi; Sapia Murgolo; Andreina Traversa; Francesco De Mastro; Marco De Sanctis; Valerio Guido Altieri; Claudio Cacace; Gennaro Brunetti; Giuseppe Mascolo (Chemosphere, 2023)

Uptake of different pharmaceuticals in soil and mycorrhizal artichokes from wastewater - Francesco De Mastro; Gennaro Brunetti; Giuseppe De Mastro; Claudia Ruta; Donato Stea; Sapia Murgolo; Cristina De Ceglie; Giuseppe Mascolo; Filomena Sannino; Claudio Cocozza; Andreina Traversa (Environmental Science and Pollution Research, 2022)

Occurrence and abundance of carbohydrates and amino compounds in sequentially extracted labile soil organic matter fractions - Hamada M. Abdelrahman; Dan C. Olk; Dana Dinnes; Domenico Ventrella; Teodoro Miano; Claudio Cocozza (Journal of Soils and Sediments, 2016)